2010
DOI: 10.1007/s10661-010-1751-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of flow field based on stable isotope geochemical characteristics in deep groundwater

Abstract: The water circulation in deep aquifers controls not only chemical composition of the groundwater, but also stable isotope composition. In order to analyze the flow field in the process of the deep groundwater circulation in different aquifers, specimens belonging to the fourth aquifer in the Quaternary (the fourth aquifer for short), the coal and sandstone cranny aquifer in the Permian, and Carboniferous (the coal catena aquifer for short), the Taiyuan group limestone aquifer in the Carboniferous (the Taiyuan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…No water sample points fall in the precipitation area, indicating that there is no direct hydraulic connection between the Taiyuan formation limestone water and atmospheric precipitation in the study area. Chen et al [30] conducted hydrogen and oxygen stable isotope tests on 30 groundwater samples from different aquifers in the Linhuan mining area, and the results showed that there was generally no direct hydraulic connection between the Taiyuan formation limestone water and other aquifers. Therefore, the analysis results of this Gibbs diagram are consistent with the research results of Chen et al…”
Section: Resultsmentioning
confidence: 99%
“…No water sample points fall in the precipitation area, indicating that there is no direct hydraulic connection between the Taiyuan formation limestone water and atmospheric precipitation in the study area. Chen et al [30] conducted hydrogen and oxygen stable isotope tests on 30 groundwater samples from different aquifers in the Linhuan mining area, and the results showed that there was generally no direct hydraulic connection between the Taiyuan formation limestone water and other aquifers. Therefore, the analysis results of this Gibbs diagram are consistent with the research results of Chen et al…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, the research on groundwater in Huaibei Coalfield has mainly focused on isotope geochemical characteristics, groundwater cycle tracing, elemental pollution degree of groundwater, and health risk assessments. A deep groundwater flow field was monitored based on stable isotope geochemical characteristics (Chen et al 2011). The water-rock interactions of deep groundwater in the Linhuan mining area and the characteristics of heavy metal content were analyzed using a Piper trigram and a Gibbs diagram (Lin et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since Craig [12] first proposed the linear relationship between the hydrogen and oxygen isotopes in global precipitation (δD = 8δ 18 O + 10) as the global meteoric water line (GMWL), hydrogen and oxygen isotopic compositions have been widely used in hydrogeochemical research [13], primarily to determine the sources of water and the types of and mechanisms underlying water-rock interactions [14,15]. The main types of water-rock interactions include ion exchange, calcite and dolomite precipitation, and the dissolution of silicates, gypsum, CO 2 , and evaporites [16][17][18].…”
Section: Introductionmentioning
confidence: 99%